2017
DOI: 10.1007/s13365-017-0518-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of CSF and serum biomarkers in HIV-1 subtype C encephalitis with CNS genetic compartmentalization—case study

Abstract: Despite the effective suppression of viremia with antiretroviral (ARV) therapy, HIV can still replicate in the CNS. This was a longitudinal study of the CSF and serum dynamics of several biomarkers related to inflammation, the blood brain barrier, neuronal injury as well IgG intrathecal synthesis in serial samples of CSF and serum from a patient infected with HIV-1 subtype C with CNS compartmentalization. The phylogenetic analyses of plasma and CSF samples in an acute phase using next-generation-sequencing (NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
(95 reference statements)
3
9
1
Order By: Relevance
“…This case presents evidence of HIV-1 subtype C neurotropism and CNS compartmentalization. Different from previous reports on HIV-1 subtypes B or C CNS compartmentalization (Canestri et al 2010; van Lelyveld et al 2010; Katlama et al 2010; Bogoch et al 2011; Bingham et al 2011; Tamarit M del et al 2012; Peluso et al 2014; de Almeida et al 2017), the present case did not meet the reported risk factors, such as low CD4+ T cell nadir and advanced immunosuppression, presence of HIV-associated dementia (HAD), and poor adherence to ART (Ritola et al 2005; Harrington et al 2009; Canestri et al 2010; Schnell et al 2010; Peluso et al 2014). …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This case presents evidence of HIV-1 subtype C neurotropism and CNS compartmentalization. Different from previous reports on HIV-1 subtypes B or C CNS compartmentalization (Canestri et al 2010; van Lelyveld et al 2010; Katlama et al 2010; Bogoch et al 2011; Bingham et al 2011; Tamarit M del et al 2012; Peluso et al 2014; de Almeida et al 2017), the present case did not meet the reported risk factors, such as low CD4+ T cell nadir and advanced immunosuppression, presence of HIV-associated dementia (HAD), and poor adherence to ART (Ritola et al 2005; Harrington et al 2009; Canestri et al 2010; Schnell et al 2010; Peluso et al 2014). …”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study support the findings of a previous study from the same group, showing that HIV-1 subtype C is as neurotropic as subtype B and also able to develop CNS HIV genetic compartmentalization (de Almeida et al 2017). Moreover, previous studies found similar frequencies of HIVC and B neurological and psychiatric manifestations as well as similar stimulation of ß-chemokines and inflammatory bio-markers in the CSF (de Almeida et al 2013, 2016a, b).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, lower HIV DNA levels in monocytes are associated with highly active antiretroviral therapy initiation within the first year of infection, suggesting that the early commencement of highly active antiretroviral therapy may improve outcomes in HAND (Murray et al, 2012;Dahl et al, 2014). In recent studies a negative correlation of the amount of CSF interferon-a and cognitive performance was found, strengthening the hypothesis that it is not direct viral infiltration but rather inflammatory responses that may be responsible for HAND (de Almeida et al, 2017). CSF pleocytosis, consisting mostly of lymphocytes and to a lesser extent of monocytes, is present early in the course of HIV infection even in neurologically asymptomatic subjects, suggesting that it is directly linked to HIV infection itself, rather than an undiagnosed opportunistic infection or neurologic complications (Ho et al, 2013).…”
Section: Human Immunodeficiency Virus Infectionmentioning
confidence: 95%
“…However, case series have reported evidence of immune activation with elevated neopterin in CSF but not plasma in both symptomatic [ 4 ] and asymptomatic cases [ 26 , 62 ] of CSF escape. Markers of BBB dysfunction are evident with elevation of the matrix metalloproteinases MMP-2, 3 and 9 and subsequent elevation of their inhibitors TIMP-1 and 2 [ 80 ]. Other inflammatory mediators are elevated such a sCD14—a marker of macrophage activation [ 80 ]; chemokines—CCL3, CCL4, CCL5 and CXCL10; cytokines—IL-1α/β, IL-1RA, IL-8, IL-10; TNF related proteins—TNFα, TNFR1, TNFR2 and TRAIL; adhesion molecules; VCAM and ICAM [ 5 , 80 ].…”
Section: The Spectrum Of Csf Escape/discordancementioning
confidence: 99%
“…Markers of BBB dysfunction are evident with elevation of the matrix metalloproteinases MMP-2, 3 and 9 and subsequent elevation of their inhibitors TIMP-1 and 2 [ 80 ]. Other inflammatory mediators are elevated such a sCD14—a marker of macrophage activation [ 80 ]; chemokines—CCL3, CCL4, CCL5 and CXCL10; cytokines—IL-1α/β, IL-1RA, IL-8, IL-10; TNF related proteins—TNFα, TNFR1, TNFR2 and TRAIL; adhesion molecules; VCAM and ICAM [ 5 , 80 ]. The presence of these inflammatory mediators show that CSF escape/discordance is associated with neuroinflammation, which is occurring in the context of a reconstituted immune system, which may be responsible for both the inflammation and viral replication by attracting HIV infected immune cells or activating latent reservoirs [ 81 ].…”
Section: The Spectrum Of Csf Escape/discordancementioning
confidence: 99%